2021
DOI: 10.1080/03067319.2021.1974424
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of the levels of dioxin-like polychlorinated biphenyls (PCBs) in soils from mechanic workshops within Nekede mechanic village, Imo State, Nigeria

Abstract: Dioxin-like polychlorinated biphenyls (DL-PCBs) are a class of persistent toxic substances with a high potential to accumulate in the soil as an organic pollutant and bioaccumulate in humans. The study determined the level and human health risk of twelve (12) DL-PCBs in soils from mechanic workshops within Nekede mechanic village (NMV), Imo State. In this study, soil samples (0-15 cm depth) were collected at four different sampling points within Nekede mechanic village. At each sampling point, composite sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The concentration of manganese in the soil sample is 149.10 ± 0.01 mg/kg. Comparing the WHO maximum allowable limit for manganese which is 2000 mg/kg with the results of sample tested for manganese, it shows that the sample is below the WHO limit [36,[46][47][48][49][50]. Mn at the location could be as a result municipal waste, sewage sludge, degradable chemicals and fertilizers being disposed.…”
Section: Heavy Metal Concentrationsmentioning
confidence: 97%
“…The concentration of manganese in the soil sample is 149.10 ± 0.01 mg/kg. Comparing the WHO maximum allowable limit for manganese which is 2000 mg/kg with the results of sample tested for manganese, it shows that the sample is below the WHO limit [36,[46][47][48][49][50]. Mn at the location could be as a result municipal waste, sewage sludge, degradable chemicals and fertilizers being disposed.…”
Section: Heavy Metal Concentrationsmentioning
confidence: 97%
“…Mobility Factor is an important indicator of heavy metal mobility and bioavailability in soil. Generally, in any sequential extraction procedure, the early fractions are the most mobile and bioavailable fractions [?, 19,34,35]. And the mobility factor value provides the relative mobility and bioavailability of these heavy metals in the contaminated dumpsite soil.…”
Section: Mobility Factors (Mf) Of Heavy Metals In the Soilsmentioning
confidence: 99%
“…To prevent additional harm to the ecosystem and food chain, ecological risk assessment is crucial for identifying potential threats and dangers posed by heavy metals to the environment. It has been observed that these hazardous heavy metals can have a variety of detrimental impacts on biological systems when exposed to them continuously through diverse pathways [44][45][46][47][48][49][50].…”
Section: Potential Ecological Risk (Eri) Assessmentmentioning
confidence: 99%